ANALISIS DAMPAK EKSPANSI KAFE & RESTORAN DI JALUR PUNCAK TERHADAP PENDAPATAN PETANI DI DESA CISARUA - Muhamad Firmansyah; Farisa Maulinam Amo (Universitas Muhammadiyah Gorontalo, 2026)
The development of cafés and restaurants along the Puncak corridor has transformed the economic structure of Cisarua Village, which previously relied primarily on highland vegetable farming. This study examines changes in farmers’ income, marketing patterns, and the factors influencing farmers’ ability to capture opportunities within the culinary supply chain. A quantitative approach was employed through a survey of 40 active farmers, complemented by in-depth interviews with 12 respondents. The findings show that farmers who successfully supplied their products directly to culinary businesses experienced an average income increase of 12–18%. In contrast, farmers who remained dependent on middlemen experienced income stagnation or even decline due to price fluctuations and the reallocation of family labor to other sectors. The study also reveals increasing pressure from agricultural land conversion and unstable demand associated with tourism activities. These findings highlight the need to strengthen farmers’ market access, empower farmer groups, and implement policies aimed at preserving agricultural land.